Program Germis sebagai Upaya Peningkatan Pengetahuan pada Pralansia dan Lansia Penderita Diabetes Melitus di Desa Sukosari Kecamatan Kauman Kabupaten Ponorogo - Rifda Husnul Istiqomah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Diabetes mellitus is a non-communicable disease characterized by elevated glucose levels accompanied by impaired protein, lipid, and carbohydrate metabolism. Ponorogo Regency is one of the regencies in East Java with a high prevalence of diabetes. Based on observations, the majority of diabetes sufferers in Sukosari Village in 2024 reached 781 cases with a fluctuating trend and were dominated by the elderly, namely 45–59 years old. The GERMIS Program is an innovation program carried out by group 9 PKL (Field Work Practice) of the Faculty of Public Health, Airlangga University in 2023. This activity aims to increase the knowledge of pre-elderly and elderly people with diabetes mellitus in Sukosari Village regarding diabetes mellitus control and the use of TOGA. Diwali activities with a pre-test followed by counseling with a lecture method and using visual media in the form of leaflets and power points and concluded with a post-test. The target of the GERMIS Program activities was 20 people with diabetes mellitus. The evaluation results showed a significant increase in knowledge among GERMIS Program participants. The average knowledge of GERMIS Program participants regarding diabetes mellitus and TOGA before the counseling was 55.00, which is included in the poor category. However, after participating in the GERMIS Program counseling, there was an increase in the average knowledge of program participants to 80.50, which is included in the good category. So it can be concluded that the GERMIS Program is effective as an effort to control diabetes mellitus in pre-elderly and elderly people in Sukosari Village, Ponorogo Regency.